2013
DOI: 10.4021/jmc1043e
|View full text |Cite
|
Sign up to set email alerts
|

Small Cell Carcinoma of the Ovary: Report of Three Cases of a Poor Prognosis Disease

Abstract: Small cell carcinoma of the ovary (SCCO) is a rare, malignant and very aggressive tumor. According to the current state of the art, no standard treatment has been established, both in terms of treatment modalities and outcomes. With the exception of some very rare cases reported in literature, the prognosis remains very poor and mortality rate extremely high. We report of three cases of SCCO with rapid progression and spreading of the disease despite multifactorial therapies. Different treatment options have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Histologically, two variants are described: one is similar to small cell carcinoma of lung, and the other one is characterized by the presence of large cell component (8).The current case showed small cell pattern only and no large cell component was found. The most common microscopic pattern is a sheet-like arrangement of small, closely packed epithelial cells.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Histologically, two variants are described: one is similar to small cell carcinoma of lung, and the other one is characterized by the presence of large cell component (8).The current case showed small cell pattern only and no large cell component was found. The most common microscopic pattern is a sheet-like arrangement of small, closely packed epithelial cells.…”
Section: Discussionmentioning
confidence: 58%
“…Small cell carcinoma of the ovary is an undifferentiated neoplasm and its histogenesis is not clear. The origin of tumor cells is epithelial, germinal, or mesenchymal, which is not clearly determined (8). The initial germ cell origin is described; however, the subsequent studies based on electron microscopy did not support this theory and instead suggested epithelial origin (9,10).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation